2020
DOI: 10.21608/eajbsd.2020.69071
|View full text |Cite
|
Sign up to set email alerts
|

Human Vermiform Appendix Of Different Age Groups

Abstract: The Journal is an Egyptian journal covering the whole field of general, experimental, systematic and applied entomology. Manuscripts generally should not exceed 30 pages (exceptions are possible, particularly in case of reviews, and should be negotiated in advance with the editors). Papers are considered by referees before acceptance. Authors will receive first editorial decision within 8 weeks from confirmed submission. All contributions are published in English. Authors whose mother tongue is not English are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…But in contrast (Ghorbani et al, 2014) found that the length of the appendix is longer in elderly people. Also there are some different findings in other study (Salih et al, 2020) which was reported that the vermiform appendix's length gradually reduced with age and that males' vermiform appendixes were somewhat longer than females'.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…But in contrast (Ghorbani et al, 2014) found that the length of the appendix is longer in elderly people. Also there are some different findings in other study (Salih et al, 2020) which was reported that the vermiform appendix's length gradually reduced with age and that males' vermiform appendixes were somewhat longer than females'.…”
Section: Discussionmentioning
confidence: 65%
“…The weight of appendix was higher in group (≥ 30) than group (21-30), (6.7 gm) and (5.8gm) respectively, so there was a gradual increased with age groups and this was agreeing with study conducted by (Mohammadi et al, 2017) in which the highest weights of appendix was (7.04gm) in group (30-39) and lowest was (2.65gm) in group (< 10). But in contrast (Salih et al, 2020) was reported that the highest weights of appendix were (7.64gm) in group (20-29) and lowest was (4.13gm) in group (60-69) because of the individual differences in immune response strength and the probable decline in the number of lymphatic follicles, their replacement by connective tissue.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation